Analysis and Design of Box Culvert: A Manual Approach - Patel, Roshan; Jamle, Sagar (International Journal of Advanced Engineering Research and Science, 2019)
Box culverts are the monolithic structure made to pass across a roadway, railway lines etc. Embankments are used to balance the flood water on both sides. Box takes various types of loads generated by water, traffic, cushion, soil etc. This work deals with complete design of box culvert manually and study the design parameters such as effect of earth pressure, depth of cushion at the top slab of culvert, factor such as braking force, Impact load, Live load, Dispersal of load through tracked or wheeled vehicle, effective width etc. In this work, study of culvert with and without cushion analyzed for different classes of IRC loadings and conclusions made on the basis of bending moments and shear forces with and without cushioning cases. This paper provides full discussion of provisions provided by Indian Standards, their justifications and considerations are taken into the account for design purpose.